EVOLUSI BUDAYA ARTEFAKTUAL SUKU ASMAT DALAM PENDEKATAN EKOTEOLOGI - Anggraheni, Wina Sulistyo Nur; Prasodjo, Tjahjono (Jambura History and Culture Journal, 2023)
The Asmat tribe has experienced significant cultural and civilizational changes in two phases, namely the arrival of missionaries in 1953 and post-independence of Indonesia in 1963. The abolition of the head-hunting tradition carried out in the mission to "humanize" the Asmat people became a cultural "defect" that stimulated the cultural evolution. The identity of the Asmat Tribe as a "wood people" create a new identity and contemporary culture oriented towards social progress based on the concept of divinity. This research is presented descriptively using qualitative research paradigm with an ecotheological approach to explaining changes of the traditional beliefs of the Asmat Tribe to the modern religious teachings.